Implementasi Metode Quantum Tahfiz Al-Qur’an (QTA) pada Siswa Program Tahfiz SMA Takhassus Al-Qur’an Kalibeber Wonosobo - Laely Nur Wahidah; Rifqi Muntaqo; Ali Imron (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This Research aims to: 1) Find out the concept of the Quantum Tahfiz Al-Qur'an method for students of SMA Takhassus Al-Qur'an memorization 2) Find out the implementation of the Quantum Tahfiz Al-Qur'an method for students of SMA Takhassus Al-Qur'an memorization 3) Find out the supporting and inhibiting factors in the implementation of the Quantum Tahfiz Al-Qur'an method. This thesis uses a qualitative approach where the type of research is field research. Data collection techniques use observation, interview, and documentation methods. The analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study show that; 1) The concept of the Quantum Tahfiz Al-Qur'an memorization method includes a combination of the Quantum Tahfiz Al-Qur'an and traditional methods, activation of the right and left brain, a schedule for studying the Koran that is adjusted to school activities; 2) Implementation of the Quantum Tahfiz Al-Qur'an method includes the activity of reciting the Koran by using the Quantum Tahfiz Al-Qur'an method, the Quantum Tahfiz Al-Qur'an method is very effective for memorizing, using rumusan; 3) The supporting factors are innovative learning, quality teaching or good teaching, a supportive environment, student motivation from coaches and teachers, adequate facilities and infrastructure. Meanwhile, inhibiting factors in the implementation of the Quantum Tahfiz Al-Qur'an method are internal factors such as laziness, lack of motivation, external factors such as situations that are less conducive, friends or parents who are less supportive, and technical factors such as inappropriate student schedules and it's hard to understand the method.